2011
DOI: 10.1159/000324458
|View full text |Cite
|
Sign up to set email alerts
|

Development of the S-303 Pathogen Inactivation Technology for Red Blood Cell Concentrates

Abstract: Pathogen inactivation systems are in use in many European countries as routine procedures. However, a pathogen inactivation system for erythrocytes is currently not available. Although significant improvements have been made to decrease the incidence of transfusion-transmitted infections, risks remain for infectious disease agents specific to red blood cell concentrates, such as parasitic infections resulting in babesiosis and malaria. The pathogen inactivation system for erythrocytes utilizes S-303 and glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 39 publications
0
79
0
Order By: Relevance
“…proflavine, aminacrine) [5]. In addition, the combination of a planar chromophore and an aminoalkylamino side chain has been used more recently to target nucleic acid, both in anticancer and antiviral applications [6].…”
Section: Introductionmentioning
confidence: 99%
“…proflavine, aminacrine) [5]. In addition, the combination of a planar chromophore and an aminoalkylamino side chain has been used more recently to target nucleic acid, both in anticancer and antiviral applications [6].…”
Section: Introductionmentioning
confidence: 99%
“…A 2 nd generation pathogen inactivation process was developed minimizing the amount of RBC-bound acridine. Preliminary results using this container (n=27) [38] indicated that the treated RBCs maintained sufficient viability (24 hour recovery rates of about 88%) and did not induce positive crossmatches [62].…”
Section: Data From Clinical Investigationsmentioning
confidence: 94%
“…The photochemical-based PRT system for erythrocytes has the capacity to effectively reduce pathogens by 4-6 log10 steps but is currently not yet available in routine use [38]. S-303 is composed of an effector (an acridine moiety), a linker (alkyl chain) and an anchor (mustard hydrochloride moiety).…”
Section: The S-303 Prt System For Rbcsmentioning
confidence: 99%
“…Therefore, the development of new pathogen reduction agents is still needed. The Intercept s303 reagent might be a good candidate, but further field trial studies are needed to analyse its inactivation potential [34]. In addition, riboflavin has also been investigated in clinical trials for packed red cell concentrates and whole blood donations [35].…”
Section: Emerging Infectionsmentioning
confidence: 99%